Amorphous Ni-P-S@FeOOH/CC catalyst for high oxygen evolution Activity: Preparation, characterization and modeling. (31st August 2022) - Hu, Zhufeng; Xu, Yinxiang; Xiang, Wenchao; Guo, Xiaodong; Tong, Yuchen; Xu, Junbo; Yang, Chao
Graphical abstract: Highlights: A high-efficiency Ni-P-S@FeOOH/CC oxygen evolution pre-catalyst was prepared by co-doping with P and S. The catalyst was modulated on FeOOH/CC precursors by simple electrodeposition. The doping structure stimulates the synergy between the binary metals, and reduces the adsorption/desorption energy of intermediates in the OER. Abstract: The oxygen evolution reaction (OER) is the key to prepare electrocatalysts for water splitting. Heteroatom doping is an effective way to improve the catalytic performance of OER by modulating the local electronic environment and stimulating the synergy. However, the complicated manufacturing methods have hindered their practical application. Herein, we demonstrate a method based on FeOOH/CC precursor to realize the preparation of Ni-P-S@FeOOH/CC catalyst through fast electrodeposition method. The overpotential of Ni-P-S@FeOOH/CC catalyst is 210 mV (10 mA cm −2 ), and still has an initial voltage of 97.35 % for 48 h. The surface area analysis shows a higher electrochemically active surface area for the amorphous structure prepared by electrodeposition method. XPS and DFT results show that the co-doping of P and S can stimulate the synergistic effect and the minimum energy of adsorption/desorption in OER process is only 0.83 eV. The strategy shows good prospects for preparing efficient OER pre-catalysts.